Phase Behaviour Physical Properties of Batyl Alcohol - Lim, Chai Seng (2004)
Batyl alcohol (monoalkylether glycerine) acts as an emulsifier when used in emulsion products, such as cosmetics creams, lotions and ointments. It is chemically stable, highly purified and safe. Although batyl alcohol is widely used in cosmetic products, little is known about its phase behaviour and rheological properties in ternary systems. Its phase behaviour in ternary systems was therefore studied at 80°C, and observed under a polarising microscope. In the ternary systems, lamellar and hexagonal areas were found in 90110 and 10010 mixtures of batyl alcohol (BA) and isopropyl myristate (IPM) and the percentage of water were from 9% - 44% wlw, respectively. They were identified by their patterns of maltese crosses and fan structures, respectively.Both of them exhibited a viscoelastic network. Further addition of either medium chain triglycerides (MCT) or propylene glycol (PG) to the system resulted in isotropic and two-phase areas being formed instead of a liquid crystalline structure. Using a combination of BA, IPM, MCT and water, an emulsion was developed. A ratio of 1 :1 MCT:water was emulsified with 5% and 10% BA. A weak viscoelastic network was formed with 5% BA but without stearic acid (Emulsion S1). With stearic acid (Emulsion S2) a strong viscoelastic network was formed with the acid acting as a co-emulsifier. No network structure was found in the emulsion containing 10% BA (Emulsion S4) as it was stabilized by the right percentage of BA. The emulsifiers adsorbed at the MCThvater interface, reducing the droplet size and increasing the viscosity, while the rest formed liquid crystalline lamellar in the continuous phase to physically trap the droplets in the network. The conductivity measured revealed that oil-in-water emulsion can conduct electric and it also shows the oil droplets encapsulated by the emulsifier in S2.